Construction of mesoporous lanthanum orthovanadate/carbon nitride heterojunction photocatalyst for the mineralization of trichloroethylene. Issue 10 (15th May 2022) - Mkhalid, Ibraheem A.; Mohamed, Reda M.; Alhaddad, Maha; Basaleh, Amal; Al-Hajji, L.A.; Ismail, Adel A.
Abstract: The search for stable, high-performance, and low-cost photocatalysts has received considerable interest. In this work, mesoporous LaVO4 nanoparticles were synthesized for the first time by applying the soft template, and g-C3 N4 nanosheets were fabricated using a hard template to design mesoporous LaVO4 /g-C3 N4 heterostructures. The synthesized photocatalysts were assessed by the mineralization of trichloroethylene (TCE) in aqueous media during visible illumination. TEM and XRD measurements verified the existence of porous g-C3 N4 with a high distribution of the monoclinic phase LaVO4 NPs (5 nm). The photocatalytic performance of the LaVO4 /g-C3 N4 heterojunction was much better than that of either LaVO4 or g-C3 N4 . 3%LaVO4 /g-C3 N4 exhibited the maximum photocatalytic ability, about 99% during a 3 h illumination at a degradation rate of 6.50 μmolL −1 min −1, which were ∼3.89- and ∼4.67-fold greater than parent LaVO4 and g-C3 N4, respectively. The first-order kinetics calculations revealed that the 3% LaVO4 /g-C3 N4 heterostructure offered the highest rate constant of 0.0113 min −1, which estimated ∼8.7 and 4.9 folds larger than LaVO4 (0.0023 min −1 ) and g-C3 N4 (0.0015 min −1 ), respectively. The importance of the LaVO4 /g-C3 N4 with superb photocatalytic efficiency was demonstrated based on the photoluminescence spectra, transient photocurrent curves, and UV–visible absorption spectra. The obtained LaVO4 /g-C3 N4 photocatalyst exhibited excellent regeneration and recyclability over five consecutive runs. The coupling of LaVO4 and g-C3 N4 with matching alignment potentials and the synergetic effect were thought to be the most interesting processes to promote photocatalytic efficiency. The obtained LaVO4 /g-C3 N4 heterojunction possesses excellent photocatalytic efficiency and is a favorable candidate for potential applications in wastewater remediation using solar energy.